NCOG-32. THE SAFETY AND EFFICACY OF DEXAMETHASONE IN THE MANAGEMENT OF GLIOMA PATIENTS. (9th November 2020) - Medikonda, Ravi; Patel, Kisha; Saleh, Laura; Srivastava, Siddhartha; Jackson, Christina; Mohan, Aditya; Weingart, Jon; Bettegowda, Chetan; Gallia, Gary; Brem, Henry; Lim, Michael
Abstract: Dexamethasone is routinely administered to glioma patients for the management of cerebral edema. Dexamethasone is associated with significant side effects including hyperglycemia, increased risk of infection, and impaired anti-tumor immune response. Despite these risks, there are no standardized guidelines for the effective use of dexamethasone in managing glioma. In this single-institution retrospective cohort study, we evaluate the effect of dexamethasone in glioma patients undergoing surgical resection on post-operative complications and overall survival. 436 patients met the inclusion criteria for this study. 46% of patients received pre-operative dexamethasone, and 90% of patients received post-operative dexamethasone. Pre-operative dexamethasone usage did not significantly affect the immediate post-operative T2 flair volume (p=0.53), however it was associated with a higher incidence of post-operative wound infection (4.0% vs 0%, p=0.002) and post-operative hyperglycemia ((p=0.02). Administration of dexamethasone in the post-operative setting did not affect the incidence of post-operative wound infection (p = 0.38) or hyperglycemia (p=0.18). It also did not affect the 3-month T2 flair volume (p=0.87). On cox proportional hazards analysis, pre-operative dexamethasone was associated with a greater hazard of death (HR=1.48; p=0.01), and post-operative dexamethasone was associated with a lower hazard of death (HR=0.20; p=0.04) after adjusting for several possible confounders. Our findings demonstrate significant differences in the safety and efficacy of pre-operative and post-operative dexamethasone in glioma patients. Routine use of pre-operative dexamethasone appears to increase the risk of post-operative complications and negatively impact survival, whereas post-operative dexamethasone improves survival and was not associated with a higher risk of steroid-related post-operative complications. These findings reaffirm a role for dexamethasone in managing cerebral edema in glioma patients, but also highlight the potential for serious negative consequences with dexamethasone use. This study provides a rationale for re-evaluating the role of dexamethasone, particularly in the pre-operative period.